The Effect of Online Learning on University Students’ Learning Motivation Hermiza Mardesci - Hermiza Mardesci (JPP (Jurnal Pendidikan dan Pembelajaran), 2020)
This study was designed to determine the effect of online learning on students’ learning motivation. Sixteen students from the Department of Food Technology, Islamic University of Indragiri, Indonesia, were involved in this study. Data collection was carried out through observation, literature review, and questionnaires. The results of this study indicate that students shared negative learning motivation responses to online learning.